The technical feasibility study on prepaid data purchase mobile application for XOX prepaid subscribers / Azlinda Mohamad - Mohamad, Azlinda (2015)
XOX is a mobile telecommunication service provider which is owned by XOX Berhad has been offering its services that include voice, SMS, and Data. Due to the current vast emergence of various types of mobile application, it is embarking on the development of mobile application to cater the demand of its subscribers. As an initial start up, XOX being realized that its Prepaid subscribers are having difficulties in remembering or recalling the Data SMS command which occurred normally during their intention of purchasing the Data service, the notion of developing the mobile application specifically for Prepaid Data Purchase came into view. Thus, in order to decide whether it is technically feasible to execute, the researcher has initiated a study to have a closer view on the issues that contributing the idea of the development. Another purpose of the research is to gather information on its technical specifications required to determine the feasibility of its development so that it may assist the organization's top management in their decision making. Content analysis on the found articles and documentations were being conducted in identifying the issues that relates to the suggestion of developing the mobile application. Interviews were being conducted in gathering data on the issues as well as the technical specifications required for the mobile application development. Based on the current Data purchase mechanism as its fundamental requirements and technical specifications obtained a prototype was being developed for user to evaluate in order to assess the technical feasibility of the mobile application development and the acceptance of user towards the mobile application. The prototype evaluation is based on hands on testing and user feedback through a set of questionnaire. The data collected underwent analysis using SPSS 16.0 by identifying the frequencies and percentage to know the recurrence of the responses. The outcome of the study comprises of the list of issues that trigger the organization to have the idea of developing the mobile application, the technical specifications required for the development, and the technical feasibility of the development. Incorporating the findings on technical specifications, and the prototype evaluation, the study found that the organization possesses adequate technical requirements that are able to cater for the mobile application development and the prototype is easy to use and preferred by the user make it technically feasible to be developed.